2003
DOI: 10.4315/0362-028x-66.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Helicobacter pylori by Bacteriocins of Lactic Acid Bacteria

Abstract: Antimicrobial activity of seven bacteriocins produced by lactic acid bacteria against Helicobacter pylori strains (ATCC 43504, Deutsche Sammlung von Mikroorganismen und Zellkulturen GmbH [DSM] 4867, DSM 9691, and DSM 10242) was investigated in vitro using a broth microdilution assay. The bacteriocins chosen for the study were nisin A; lacticins A164, BH5, JW3, and NK24; pediocin PO2; and leucocin K. Antimicrobial activity of the bacteriocins varied among the H. pylori strains tested, of which strain ATCC 43504… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 38 publications
1
82
0
6
Order By: Relevance
“…It has been documented that the human probiotic intestinal microbiota L. johnsonii NCC 533, L. casei Shirota, and L. acidophilus LB display direct antagonistic activity in vitro against the gastritisassociated bacterium H. pylori ( Fig. 1 (113,(152)(153)(154). The molecule(s) present in L. acidophilus LB CFCS that exerts bactericidal activity against H. pylori remain to be identified.…”
Section: Direct Activities Against H Pylorimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented that the human probiotic intestinal microbiota L. johnsonii NCC 533, L. casei Shirota, and L. acidophilus LB display direct antagonistic activity in vitro against the gastritisassociated bacterium H. pylori ( Fig. 1 (113,(152)(153)(154). The molecule(s) present in L. acidophilus LB CFCS that exerts bactericidal activity against H. pylori remain to be identified.…”
Section: Direct Activities Against H Pylorimentioning
confidence: 99%
“…The generally held view is that bacteriocins exhibit less potential as chemotherapeutics for infections with Gram-negative pathogens. However, it should be noted that several bacteriocins and bacteriocin-like molecules produced by probiotic Lactobacillus strains have been also found to be active against the growth of several Gram-negative gastric or enterovirulent bacterial pathogens, including H. pylori, EHEC, Shigella, Salmonella, and Campylobacter (112)(113)(114)(115)(116).…”
Section: Direct Activities Against Enterovirulent Bacteriamentioning
confidence: 99%
“…Kim et al 28 evaluated, by microdilution assay, the anti-H. pylori activity of seven bacteriocins produced by lactic acid bacteria, including nisin A, pediocin PO2, leucocin K and various types of lacticins. Lacticins A164 and BH5 produced by strains of L. lactis had the most potent activity, with minimum inhibitory concentrations varying from 0.097-0.390 mg/L to 12.5-25 mg/L depending on the strains of H. pylori tested, indicating a strain-dependent sensitivity of this pathogen.…”
mentioning
confidence: 99%
“…responsible for the inhibitory activity. Kim et al (2003) suggested that lacticins A164 and BH5 produced by Lactococcus lactis subsp. lactis A164 and L. lactis BH5, respectively, showed the anti-H. pylori activity of lacticin A164 was dependent on initial inoculum size as well as concentration of the bacteriocin added.…”
Section: Resultsmentioning
confidence: 99%